Practical power plant engineering : a guide for early career engineers - Bedalov, Zark (Wiley, 2020)
"This book adds to the theoretical knowledge of engineering students and prepares them for the job market including the search for a position and how best to interview when they find one. A project may be built by mechanical engineers, but it is made operational by electrical engineers, as the electricity is the blood that flows through the plant components. The book offers the authors' decades of practical experience from working in a number of industries with ever-changing technologies and by associating with many experienced engineers from electrical and other engineering backgrounds. It comprises 26 chapters covering all aspects of electrical engineering related to the design and development of power and heavy industrial projects; based on examples, calculations, standards, illustrations, and common sense engineering practices"--